A Study of End-to-End Web Access Failures - Ramabhadran, Sriram; Agarwal, Sharad; Padhye, Jitu; Padmanabhan, Venkat (CoNEXT, 2006)
We present a study of end-to-end web access failures in the Internet. Part of our characterization of failures is based on directly observable end-to-end information. We also present novel analyses that reveal aspects of end-to-end failures that would be hard to discern otherwise. First, we combine end-to-end failure observations across a large number of clients to classify failures as server-related or client-related. Second, we correlate failures attributed to a client or server with BGP churn for the corresponding IP address prefix(es), to shed light on the end-to-end impact of BGP instability. Our study is based on failure observations during a month-long experiment involving 134 client hosts (across Planet-Lab, commercial dialup and broadband ISPs, and a corporate network) repeatedly accessing 80 websites. We find that the median failure rate of web accesses is about 1.5%, which is non-negligible. About 34–42% of the web access failures are due to DNS problems, primarily due to the inability of the client to connect to its local DNS server. The majority of the remaining failures are due to TCP connection establishment failures. Also, by correlating failure observations across clients and servers, we find that server-side problems are the dominant cause of TCP connection failures.